A Comparison of Classroom Management and Lesson Scheduling Elementary School in Southeast Asia: Implications for Student Learning Processes and Outcomes - Cahya, Aulia Ihza; Iskandar, Sofyan; Abidin, Yunus; Dewi, Dinie Anggraeni (Journal of Cultural Analysis and Social Change, 2025)
This study aims to analyze the differences in classroom management, lesson planning, student learning processes, and overall impressions of primary education in Indonesia, Malaysia, Thailand, and the Philippines. The method used was a comparative descriptive qualitative method where data were collected through interviews with teachers from the four countries and analyzed comparatively to identify patterns, challenges and strengths in each country's primary education system. The results show that Indonesia and the Philippines emphasize a more democratic approach to classroom management, while Thailand uses a more authoritative model and Malaysia is somewhere in between with a balance between discipline and student engagement. In terms of lesson planning, Indonesia and Malaysia use a flexible structure while still following national curriculum guidelines, while Thailand is more-strict and the Philippines has the most dynamic system. Learning and assessment methods also vary, with Indonesia and Thailand combining written exams and project-based assessments, Malaysia focusing more on standardized assessments, and the Philippines emphasizing reflective assessments and real-world applications. The conclusion of this study confirms that despite differences in educational approaches, all countries face similar challenges, such as limited resources, differences in students' learning pace, and gaps in access to educational technology. Therefore, the study recommends the integration of more flexible learning strategies, improved teacher training, and more adaptive curriculum reforms to improve the effectiveness and inclusiveness of basic education systems in Southeast Asia.